Graphite composite material, preparation method thereof and secondary battery

By doping metal elements and intercalating metal oxides in graphite and covering multi-wall carbon nanotubes and amorphous carbon, graphite composite materials with high capacity and excellent cycling performance are prepared, solving the consistency and stability of existing graphite materials in cell applications.

CN119650626AActive Publication Date: 2025-03-18GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD

Patent Information

Application Number
CN202411731621.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

As the negative electrode material of lithium-ion batteries, graphite has problems such as poor dispersion between materials, poor interface bonding and lack of synergistic effects, which affects battery consistency, ion transmission efficiency and cyclic stability.

Method used

Through doping, intercalation and surface modification, a three-layer graphite composite material is prepared. The core is metallic element-doped metal oxide embedded between the graphite sheets, and the shell is multi-walled carbon nanotubes and amorphous carbon to form a stable core-shell structure.

Benefits of technology

The graphite composite material exhibits high capacity and excellent cycling performance, combining the advantages of high capacity of metal oxides and high cycling stability of graphite, improving lithium storage performance through doping elements, and suppressing volume expansion through core-shell and intercalation structure to improve cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650626A_ABST
    Figure CN119650626A_ABST
Patent Text Reader

Abstract

The invention provides a graphite composite material, a preparation method thereof and a secondary battery, and relates to the technical field of lithium ion battery negative electrode materials. The graphite composite material comprises an inner core and a shell layer, the inner core comprises metal element doped metal oxide and graphite, the metal element doped metal oxide is embedded between sheet layers of the graphite, the shell layer comprises multi-walled carbon nanotubes and amorphous carbon, and the multi-walled carbon nanotubes are distributed in the amorphous carbon in a 3D net shape. According to the invention, by introducing the doping element, the lithium intercalation active sites of the metal oxide are increased, so that the lithium storage performance of the graphite composite material is improved; through the construction of a core-shell and intercalation structure, the volume expansion of the metal oxide is inhibited, so that the cycling stability of the graphite composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a graphite composite material, a preparation method thereof and a secondary battery, and relates to the technical field of new material preparation. Background Art

[0002] Currently, graphite is widely used as a negative electrode material for lithium-ion batteries, due to its stable chemical properties, high conductivity and moderate specific capacity, in the fields of 3C, power and energy storage. However, with the development of the market, the use of graphite as a negative electrode material alone has gradually failed to meet the diverse needs. For this reason, the industry has begun to seek new negative electrode materials to improve the overall performance of lithium-ion batteries.

[0003] Among the emerging negative electrode materials, silicon-based materials, tin-based materials and metal compounds have attracted widespread attention due to their higher theoretical specific capacity. However, these new materials are also accompanied by significant disadvantages. For example, large volume effects and low electrical conductivity seriously affect the cycle and rate performance of the materials. In order to overcome these shortcomings, the mainstream method is to mix a small amount of new materials into graphite, aiming to obtain the advantages of both at the same time, thereby seeking a balance between the capacity, cycle and rate performance of the materials. However, simple mechanical mixing has many shortcomings, such as poor dispersion between materials, loose interface bonding and lack of synergistic effect. This seriously affects battery consistency, ion transfer efficiency and cycle stability.

[0004] In response to the above problems, the industry urgently needs to develop more sophisticated and synergistic composite strategies. For example, through micro-nano-sized composite technology, the combination of graphite and new materials can be optimized, which can not only increase the contact area between materials and improve the transmission efficiency of lithium ions and electrons, but also suppress the negative effects of high expansion materials through a strengthened interface. In addition, the development of surface modification technology is also an effective way to solve the stability problem of composite materials. By coating the surface of the composite material with highly conductive and high tensile strength materials, the conductivity and structural integrity of the composite material can be effectively enhanced. In short, although simple mechanical mixing provides a certain solution to the improvement of battery performance, in order to give full play to the advantages of various negative electrode materials, it is also necessary to carry out systematic optimization and innovation in many aspects such as material size, structure and coating engineering, so as to meet the current battery technology for high energy density, fast charging and long life. Comprehensive demand. Summary of the invention

[0005] In order to solve the above problems, the present invention prepares a graphite composite material by means of doping, intercalation and surface modification. When the graphite composite material is used as a negative electrode material in the preparation of a secondary battery, it exhibits high capacity and excellent cycle performance. The specific scheme is as follows:

[0006] Firstly, the present invention provides a graphite composite material, comprising a core and a shell, wherein the core comprises metal element doped metal oxide and graphite, the metal element doped metal oxide is embedded between graphite sheets, and the shell comprises multi-walled carbon nanotubes and amorphous carbon.

[0007] Preferably, the graphite composite material comprises at least one of the following features (i) to (ix):

[0008] (a) The mass ratio of graphite to metal oxide is 100:(10-100);

[0009] (ii) the mass ratio of graphite to amorphous carbon is 100:(1-20);

[0010] (iii) the mass ratio of amorphous carbon to multi-walled carbon nanotubes is 100:(1-15);

[0011] (iv) The particle size of graphite is 3-30 μm;

[0012] (V) Shell thickness is 100nm-2μm;

[0013] (6) The graphite is artificial graphite;

[0014] (VII) The metal doping element is one or more of manganese, cobalt and nickel; the doping amount of the metal element is 1%-15%;

[0015] (8) The metal oxide is one or more of the oxides of titanium, vanadium, chromium, zirconium, niobium and molybdenum;

[0016] (IX) Multi-walled carbon nanotubes have an outer diameter of less than 200 nm and a length of less than 10 μm.

[0017] Preferably, the graphite composite material comprises at least one of the following features (1) to (4):

[0018] (1) The first reversible capacity of the graphite composite material is greater than 410 mAh / g;

[0019] (2) The first coulombic efficiency of the graphite composite material is greater than 83%;

[0020] (3) The 50-week capacity retention rate of graphite composite materials is greater than 96%;

[0021] (4) The expansion rate of the graphite composite material is less than 35%.

[0022] Preferably, in the shell layer of the graphite composite material, the multi-walled carbon nanotubes are distributed in the amorphous carbon in a 3D network, and the amorphous carbon is uniformly coated on the surface of the core.

[0023] Second, the present invention provides a method for preparing the above-mentioned graphite composite material, comprising the following steps:

[0024] S1. Intercalant pretreatment: preparing bromide / metal oxide mixed fine powder and coke aggregate;

[0025] S2. Preparation of intercalated graphite precursor: mixing bromide / metal oxide mixed fine powder with coke aggregate to obtain intercalated graphite precursor;

[0026] S3, preparation of intercalated graphite: placing the intercalated graphite precursor into a crucible, performing a programmed heat treatment, and obtaining metal-doped metal oxide intercalated graphite after natural cooling;

[0027] S4, pretreatment of multi-walled carbon nanotubes: immersing the multi-walled carbon nanotubes in a mixed solution of nitric acid / concentrated sulfuric acid, heating and stirring in a water bath, and firstly separating and obtaining functionalized multi-walled carbon nanotubes;

[0028] S5. Preparation of coating layer precursor: dissolving pretreated multi-walled carbon nanotubes and polyvinyl pyrrolidone in N,N-dimethylformamide solution, and ultrasonically mixing to obtain solution A; dissolving dopamine hydrochloride and tris(hydroxymethyl)aminomethane in deionized water and adjusting the pH to 8.0-9.0 to obtain brown-yellow solution B; rapidly adding solution B to solution A and stirring for the first time to obtain solution C; adding metal-doped metal oxide intercalated graphite to solution C and continuing stirring for the second time; and separating for the second time to obtain coating layer precursor;

[0029] S6. Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: placing the product obtained in step S5 in a tubular furnace, under argon protection, and naturally cooling to room temperature after heat treatment to obtain a multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite composite material.

[0030] Preferably, in S1, coke aggregate is prepared by crushing coke into aggregate with D50=1-25 μm by roller mill; bromide / metal oxide mixed fine powder is prepared by mixing metal oxide and bromide at a ratio of 100:

[0031] The (5-50) mass ratio is placed in a ball mill and ball milled at 100-400 rpm for 1-20 h to obtain the product.

[0032] Preferably, in S2, the mass ratio of coke aggregate to bromide / metal oxide mixed fine powder is 100:(10-125), and batch mixing is carried out using a batch mixing machine for 2-3 hours.

[0033] Preferably, in S3, the programmed heat treatment comprises: heating to 200°C at 5-8°C / min in a medium frequency furnace, keeping the temperature for 2-2.5h, and then heating to 2000-3200°C at 8-15°C / min, and keeping the temperature for 1-1.5h.

[0034] Preferably, in S4, in the nitric acid / concentrated sulfuric acid mixed solution, the volume ratio of nitric acid / concentrated sulfuric acid is (2.5-3):1; the water bath temperature is 80-85°C, the stirring speed is 100-400rpm, and the treatment time is 2-5h.

[0035] Preferably, the first separation in S4 refers to collecting the solid by suction filtration, washing the obtained solid with deionized water for 3-5 times, and then drying at 80° C. for 12 h.

[0036] Preferably, in S5, the ultrasonic mixing time is 0.5-2h, the first stirring is carried out at room temperature, the stirring speed is 300-800rpm, and the time is 0.5-2h; the second stirring is carried out at room temperature, the stirring speed is 50-200rpm, and the time is 12-48h.

[0037] Preferably, the second separation in S5 refers to collecting the solid by suction filtration, washing with deionized water for 3-5 times to a pH of 6.5-7.5, and drying at 80-85° C. for 12 h.

[0038] Preferably, in S6, the heat treatment refers to heating the temperature to 300-500°C at a heating rate of 5°C / min and keeping the temperature for 3-3.5h.

[0039] Third, the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material comprises the aforementioned graphite composite material or a graphite composite material prepared by the aforementioned graphite composite material preparation method.

[0040] Beneficial effects of the present invention:

[0041] The present invention provides a graphite composite material, a preparation method thereof and a secondary battery. The composite material has a three-layer structure, wherein the innermost layer is a metal oxide doped with a metal element, which is embedded between graphite sheets to form a special metal oxide intercalated graphite structure. The outermost layer is a multi-walled carbon nanotube / amorphous carbon layer, which is uniformly coated on the graphite surface to form a stable core-shell structure. The composite material prepared by the present invention combines the advantages of high capacity of metal oxides and high cycle stability of graphite. By introducing doping elements, the lithium insertion active sites of metal oxides are increased, thereby improving the lithium storage performance of the graphite composite material. By constructing the core-shell and intercalation structures, the volume expansion of metal oxides is suppressed, thereby improving the cycle stability of the graphite composite material.

[0042] Specifically:

[0043] 1) The present invention uses a high-temperature graphitization process to complete the preparation of metal oxide / graphite composite materials. In the heating stage, the crystal water in the mixture of coke / metal oxide / bromide is removed; in the graphitization and heat preservation stage, the graphitization of coke, the transformation of metal oxide to a molten state, and the decomposition of bromide to produce bromine gas and metal compounds are completed; in the cooling stage, the metal compound and the metal oxide are fused to transform into metal-doped metal oxides, while bromine gas is dynamically embedded and de-embedded in the graphitized coke, which effectively expands the graphite interlayer spacing, thereby assisting the molten metal-doped metal oxide to complete the intercalation. The whole process is completed in one step, making full use of the energy consumption of the graphitization process, and has the advantages of low cost and being conducive to industrial production.

[0044] 2) The present invention uses polyvinyl pyrrolidone as a dispersant, and uniformly mixes the pretreated multi-walled carbon nanotubes, dopamine hydrochloride and intercalated graphite by ultrasound and stirring. Under appropriate pH conditions, dopamine undergoes a polymerization reaction, and the polydopamine wrapped with the multi-walled carbon nanotubes is uniformly coated on the surface of the intercalated graphite. Subsequently, a multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite is prepared by a carbonization process. The multi-walled carbon nanotube / carbon coating prepared by the present invention has the advantages of good coating uniformity and high tensile strength. Multi-walled carbon nanotubes and amorphous carbon form a stable structure similar to a steel bar / cement structure. The multi-walled carbon nanotubes are embedded in the amorphous carbon, providing a good three-dimensional conductive network and mechanical properties for the amorphous carbon layer, thereby improving the conductivity of the material while alleviating the volume expansion of the intercalated graphite during the circulation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram of the structure of the graphite composite material of the present invention;

[0046] Figure 2 This is the SEM image of the graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0049] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0050] Example 1 Multi-walled carbon nanotubes / carbon-coated cobalt-doped chromium oxide intercalated graphite (intermediate frequency furnace 2500°C)

[0051] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0052] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of needle coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0053] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0054] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0055] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0056] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0057] Example 2 Multi-walled carbon nanotubes / carbon-coated cobalt-doped chromium oxide intercalated graphite (intermediate frequency furnace 2300°C)

[0058] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0059] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0060] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2300°C at 10°C / min, kept at this temperature for 1 h, and cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0061] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0062] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0063] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0064] Example 3 Multi-walled carbon nanotubes / carbon-coated cobalt-doped chromium oxide intercalated graphite (intermediate frequency furnace 2700°C)

[0065] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0066] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0067] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2700°C at 10°C / min, kept at this temperature for 1 h, and cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0068] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0069] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0070] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0071] Example 4 Multi-walled carbon nanotube / carbon-coated cobalt-doped chromium oxide intercalated graphite (mass ratio of CoBr2 / Cr2O3 mixture to petroleum coke is 9:40)

[0072] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 15 g CoBr2 and 75 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0073] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0074] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0075] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0076] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0077] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0078] Example 5 Multi-walled carbon nanotube / carbon-coated cobalt-doped chromium oxide intercalated graphite (mass ratio of CoBr2 / Cr2O3 mixture to petroleum coke is 9:10)

[0079] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 60 g CoBr2 and 300 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0080] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0081] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0082] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0083] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0084] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0085] Example 6 Multi-walled carbon nanotubes / carbon-coated cobalt-doped chromium oxide intercalated graphite (mass ratio of multi-walled carbon nanotubes to dopamine hydrochloride 1:20)

[0086] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0087] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0088] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0089] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0090] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 20 mg of dopamine hydrochloride and 30 mg of trishydroxymethylaminomethane are dissolved in 20 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 20 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0091] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0092] Example 7 Multi-walled carbon nanotubes / carbon-coated cobalt-doped chromium oxide intercalated graphite (the mass ratio of multi-walled carbon nanotubes to dopamine hydrochloride is 1:60)

[0093] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0094] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0095] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Co-doped Cr2O3 intercalated graphite;

[0096] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0097] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 60 mg of dopamine hydrochloride and 90 mg of trishydroxymethylaminomethane are dissolved in 60 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 60 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0098] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 intercalated graphite.

[0099] Comparative Example 1 Multi-walled carbon nanotube / carbon-coated cobalt-doped chromium oxide / graphite mixture (without intercalation structure)

[0100] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0101] (2) Preparation of cobalt-doped chromium trioxide: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) is placed in a crucible, heated to 200°C at 5°C / min in a medium frequency furnace, kept warm for 2 h, then heated to 2500°C at 10°C / min, kept warm for 1 h, and cooled naturally to obtain cobalt-doped chromium trioxide;

[0102] (3) Preparation of graphite: The petroleum coke aggregate obtained in step (1) is placed in a crucible, heated to 200° C. at 5° C. / min in a medium frequency furnace, kept at this temperature for 2 h, then heated to 2500° C. at 10° C. / min, kept at this temperature for 1 h, and then cooled naturally to obtain artificial graphite;

[0103] (4) Preparation of cobalt-doped chromium trioxide / graphite: The cobalt-doped chromium trioxide obtained in step (2) and the graphite obtained in step (3) are placed in a batch mixer at a mass ratio of 9:20, and mixed for 2 hours to obtain a cobalt-doped chromium trioxide / graphite mixture;

[0104] (5) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), in an 80°C water bath, stirred at 200 rpm for 3 h, then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes;

[0105] (6) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the product obtained in step (4) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0106] (7) Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide / graphite mixture: The product obtained in step (6) is placed in a tubular furnace, and under argon protection, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 h, and naturally cooled to room temperature to obtain a multi-walled carbon nanotube / carbon-coated Co-doped Cr2O3 / graphite mixture.

[0107] Since the cobalt-doped chromium oxide and the artificial graphite are only mechanically mixed in step (4), no intercalation reaction occurs in this comparative example.

[0108] Comparative Example 2 Cobalt-doped chromium oxide intercalated graphite (without coating layer)

[0109] (1) Raw material pretreatment: Use a roller mill to crush petroleum coke into aggregates with a D50 of 8-9 μm, put 30 g CoBr2 and 150 g Cr2O3 into a ball mill, and mill at 300 rpm for 10 h to obtain a uniform CoBr2 / Cr2O3 mixed fine powder;

[0110] (2) Preparation of intercalated graphite precursor: The CoBr2 / Cr2O3 mixed fine powder obtained in step (1) and 400 g of petroleum coke aggregate were placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0111] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) was placed in a crucible, heated to 200°C at 5°C / min in a medium frequency furnace, kept warm for 2 h, then heated to 2500°C at 10°C / min, kept warm for 1 h, and cooled naturally to obtain Co-doped Cr2O3 intercalated graphite.

[0112] Comparative Example 3 Multi-walled carbon nanotubes / carbon-coated chromium oxide intercalated graphite (no element doping)

[0113] (1) Raw material pretreatment: Use a roller mill to crush the petroleum coke into aggregates with a D50 of 8-9 μm, put 180 g of Cr2O3 into a ball mill, and ball mill at 300 rpm for 10 h to obtain Cr2O3 fine powder;

[0114] (2) Preparation of intercalated graphite precursor: The Cr2O3 fine powder obtained in step (1) and 400 g of petroleum coke aggregate are placed in a batch mixer and mixed for 2 h to obtain an intercalated graphite precursor;

[0115] (3) Preparation of intercalated graphite: The intercalated graphite precursor obtained in step (2) is placed in a crucible, heated to 200°C in a medium frequency furnace at 5°C / min, kept at this temperature for 2 h, then heated to 2500°C at 10°C / min, kept at this temperature for 1 h, and then cooled naturally to obtain Cr2O3 intercalated graphite;

[0116] (4) Pretreatment of multi-walled carbon nanotubes: 300 mg of multi-walled carbon nanotubes were immersed in 50 mL of a mixed solution of nitric acid / concentrated sulfuric acid (3:1), placed in an 80°C water bath, and stirred at 200 rpm for 3 h. The mixture was then collected by suction filtration, washed with deionized water for 3-5 times, and then dried at 80°C for 12 h to obtain functionalized multi-walled carbon nanotubes.

[0117] (5) Preparation of coating layer precursor: Take 1 mg of pretreated multi-walled carbon nanotubes and 6 mg of polyvinyl pyrrolidone and dissolve them in 10 mL of N,N-dimethylformamide solution, and ultrasonicate for 1 hour. Solution A is obtained. 40 mg of dopamine hydrochloride and 60 mg of trishydroxymethylaminomethane are dissolved in 40 mL of deionized water, and the pH of the solution is adjusted to 8.5 with sodium hydroxide solution to obtain a brown-yellow solution B. Then, solution A is quickly added to solution B, and stirred at 500 rpm for 1 hour at room temperature to obtain solution C. Then, take 40 mg of the intercalated graphite prepared in step (3) and add it to solution C, continue stirring at 100 rpm for 24 hours, then wash with deionized water 3-5 times, and dry at 80°C for 12 hours to obtain a coating layer precursor;

[0118] (6) Preparation of multi-walled carbon nanotube / carbon-coated metal oxide intercalated graphite: The product obtained in step (5) is placed in a tubular furnace, and under the protection of argon, the temperature is increased to 400°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain multi-walled carbon nanotube / carbon-coated Cr2O3 intercalated graphite.

[0119] Electrochemical performance test:

[0120] 1. Pole preparation:

[0121] The final product obtained by the above-mentioned embodiment and comparative example is used as the active material, polyvinylidene fluoride is used as the binder, and carbon black Super-P is used as the conductive agent. The three are mixed in a mass ratio of 91:7:2, and an appropriate amount of N-methylpyrrolidone solvent is added to form a uniform slurry, which is then coated on the copper foil. The obtained copper foil is placed in an oven at 100°C and baked for 2 hours. After being taken out and stamped, an electrode sheet with a diameter of 14 mm is obtained. Finally, the obtained electrode sheet is baked in a vacuum box at 105°C for 4 hours, and then quickly placed in a glove box to wait for assembly into a button battery.

[0122] 2. Button battery assembly and testing:

[0123] The obtained pole piece was used as the working electrode, the lithium sheet as the counter electrode, the polypropylene microporous membrane as the diaphragm, and the electrolyte was 1MLiPF6+EC:DEC:DMC=1:1:1 (volume ratio), and assembled into a CR2430 button cell in an argon atmosphere glove box. The charge and discharge test of the button cell was carried out on the battery test system of Wuhan Blue Electric Electronics Co., Ltd. Under normal temperature conditions, 0.1C constant current charge and discharge were adopted, and the charge and discharge voltage was limited to 0.005V to 2.0V. The first reversible specific capacity, the first coulomb efficiency, the 50-week capacity retention rate and the pole piece full charge expansion rate were tested. Among them, the 50-week cycle capacity retention rate = the 50th week cycle discharge capacity / the first week discharge capacity × 100%, the full charge expansion rate of the negative pole piece = (the thickness of the pole piece after full charge-the thickness of the pole piece before charging) / the thickness of the pole piece before charging × 100%, and the obtained data are shown in Table 1.

[0124] Table 1 Electrochemical performance test results of examples and comparative examples

[0125]

[0126] Table 1 shows the electrochemical performance test results of the samples obtained in the embodiments and comparative examples. It can be seen from Table 1 that the graphite composite materials prepared in Examples 1 to 7 have excellent performance in terms of capacity, first effect, capacity retention rate and full-charge expansion rate of the pole piece. In terms of the first reversible capacity, the first reversible capacity of Examples 1-7 is greater than 410mAh / g, far exceeding the first reversible capacity of the current mainstream artificial graphite negative electrode (340-360mAh / g), which is mainly due to the high capacity provided by the metal oxide embedded between the graphite layers. In Comparative Examples 1-3, the first reversible capacity of Comparative Example 3 without element doping is the lowest (only 365.1mAh / g). This phenomenon shows that element doping has a positive effect on the improvement of the capacity of metal oxides. The possible reason is that the lone pair of electrons formed by element doping enhances the electronic conductivity of the metal oxide. In addition, the introduction of heterogeneous elements causes a large number of lattice defects to be generated inside the metal oxide, thereby increasing its lithium insertion active sites, and thus significantly improving the lithium storage performance of the material; in terms of the first efficiency, the first efficiency of Examples 1-7 is higher than 83%, which is higher than that of Comparative Example 1 (72.8%) without intercalation structure. This can be attributed to the special intercalation structure of the embodiments, which significantly reduces the contact between the metal oxide and the electrolyte, thereby inhibiting the lithium loss caused by the side reaction between the metal oxide and the electrolyte; in terms of capacity retention rate, the capacity retention rate of Examples 1-7 is higher than 96% after 50 cycles at 1C, while that of Comparative Example 1 without intercalation structure is higher than that of Comparative Example 1 (72.8%). The capacity retention rates of Comparative Example 1 with an intercalation structure and Comparative Example 2 without a coating layer are both lower than 76%, which indicates that the restrictions of the intercalation structure and the coating layer during the cycle effectively improve the capacity attenuation caused by the volume effect of the metal oxide or the leakage of the graphite sheet; in terms of the full-charge expansion rate of the electrode, the expansion rates of Examples 1-7 are all lower than 35%, while the expansion rates of Comparative Example 1 without an intercalation structure and Comparative Example 2 without a coating layer are both higher than 50%. This result strongly proves the inhibitory effect of the intercalation structure and the coating layer on the volume expansion of the composite material during the charge and discharge process, thereby effectively ensuring the cycle stability of the material.

[0127] In summary, the multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite composite material prepared by the method provided by the present invention is a negative electrode material with high capacity and excellent cycle performance.

[0128] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0129] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and do not deviate from the purpose of the invention, they can creatively design methods and embodiments similar to the technical solution, which should fall within the protection scope of the present invention.

Claims

1. A graphite composite material, characterized in that: The invention comprises a core and a shell layer, wherein the core comprises metal oxide doped with metal elements and graphite, the metal oxide doped with metal elements is embedded between the graphite sheets, and the shell layer comprises multi-walled carbon nanotubes and amorphous carbon.

2. The graphite composite material according to claim 1, characterized in that: Contains at least one of the following features (i) to (ix): (i) the mass ratio of the graphite to the metal oxide is 100:(10-100); (ii) the mass ratio of the graphite to the amorphous carbon is 100:(1-20); (iii) the mass ratio of the amorphous carbon to the multi-walled carbon nanotubes is 100:(1-15); (iv) the particle size of the graphite is 3-30 μm; (V) The shell layer thickness is 100 nm to 2 μm; (vi) the graphite is artificial graphite; (VII) The metal doping element is one or more of manganese, cobalt, and nickel, and the doping amount of the metal element is 1%-15%; (8) The metal oxide is one or more of the oxides of titanium, vanadium, chromium, zirconium, niobium and molybdenum; (IX) The multi-walled carbon nanotube has an outer diameter of less than 200 nm and a length of less than 10 μm.

3. The graphite composite material according to claim 1, characterized in that: Contains at least one of the following features (1) to (4): (1) The first reversible capacity of the graphite composite material is greater than 410 mAh / g; (2) The first coulombic efficiency of the graphite composite material is greater than 83%; (3) The 50-week capacity retention rate of the graphite composite material is greater than 96%; (4) The expansion rate of the graphite composite material is less than 35%.

4. The graphite composite material according to claim 1, characterized in that: In the shell layer of the graphite composite material, the multi-walled carbon nanotubes are distributed in the amorphous carbon in a 3D network, and the amorphous carbon is uniformly coated on the surface of the core.

5. A method for preparing the graphite composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Intercalant pretreatment: preparing bromide / metal oxide mixed fine powder and coke aggregate; S2. Preparation of intercalated graphite precursor: mixing bromide / metal oxide mixed fine powder with coke aggregate to obtain intercalated graphite precursor; S3, preparation of intercalated graphite: placing the intercalated graphite precursor into a crucible, performing a programmed heat treatment, and obtaining metal-doped metal oxide intercalated graphite after natural cooling; S4, pretreatment of multi-walled carbon nanotubes: immersing the multi-walled carbon nanotubes in a mixed solution of nitric acid / concentrated sulfuric acid, heating and stirring in a water bath, and firstly separating and obtaining functionalized multi-walled carbon nanotubes; S5. Preparation of coating layer precursor: dissolving the pretreated multi-walled carbon nanotubes and polyvinyl pyrrolidone in N,N-dimethylformamide solution, and ultrasonically mixing to obtain solution A; dissolving dopamine hydrochloride and tris(hydroxymethyl)aminomethane in deionized water and adjusting the pH to 8.0-9.0 to obtain brown-yellow solution B; Rapidly add solution B to solution A and stir for the first time to obtain solution C; Adding the metal-doped metal oxide intercalated graphite to solution C and continuing stirring for a second time; The second separation yields the coating layer precursor; S6. Preparation of multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite: placing the product obtained in step S5 in a tubular furnace, under argon protection, and naturally cooling to room temperature after heat treatment to obtain a multi-walled carbon nanotube / carbon-coated metal-doped metal oxide intercalated graphite composite material.

6. The method for preparing the graphite composite material according to claim 5, characterized in that: In S1, the preparation of coke aggregate: using a roller mill to crush coke into aggregate with D50 = 1-25 μm; the preparation of bromide / metal oxide mixed fine powder: putting metal oxide and bromide into a ball mill according to a mass ratio of 100: (5-50), and ball milling at 100-400 rpm for 1-20 hours to obtain.

7. The method for preparing the graphite composite material according to claim 5, characterized in that: In S2, the mass ratio of coke aggregate to bromide / metal oxide mixed fine powder is 100:(10-125), and the batch mixing is carried out by a batch mixing machine for 2-3 hours; In S3, the programmed heat treatment includes: heating to 200°C at 5-8°C / min in a medium frequency furnace, keeping the temperature for 2-2.5h, and then heating to 2000-3200°C at 8-15°C / min, and keeping the temperature for 1-1.5h.

8. The method for preparing the graphite composite material according to claim 5, characterized in that: In S4, the volume ratio of nitric acid / concentrated sulfuric acid in the nitric acid / concentrated sulfuric acid mixed solution is (2.5-3):1; the water bath temperature is 80-85°C, the stirring speed is 100-400rpm, and the processing time is 2-5h; the first separation in S4 refers to collecting the solid by suction filtration, washing the obtained solid with deionized water for 3-5 times, and then drying at 80°C for 12h.

9. The method for preparing the graphite composite material according to claim 5, characterized in that: In S5, the ultrasonic mixing time is 0.5-2h, the first stirring is carried out at room temperature, the stirring speed is 300-800rpm, and the time is 0.5-2h; the second stirring is carried out at room temperature, the stirring speed is 50-200rpm, and the time is 12-48h; the second separation in S5 is to collect the solid by suction filtration, wash it with deionized water 3-5 times to pH 6.5-7.5, and dry it at 80-85℃ for 12h; in S6, the heat treatment refers to heating to 300-500℃ at a heating rate of 5℃ / min and keeping it warm for 3-3.5h.

10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material comprises the graphite composite material according to any one of claims 1 to 4 or a graphite composite material prepared by the method for preparing a graphite composite material according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Graphite composite material and application and preparation method thereof, and lithium ion battery

    CN107017397A

  • Carbon-coated exfoliated metal sulfide composite graphite nanosheet battery negative electrode material and preparation method thereof

    CN115692647A

  • Preparation method and application of graphene / carbon nanotube composite conductive agent

    CN115986118A

  • Preparation method and application of low-temperature additive for lithium / sodium battery capable of being operated at low temperature

    CN117199537A

  • Carbonaceous lithium ion battery negative electrode material with nuclear shell structure and producing method thereof

    CN1848490A

Cited By

  • Lithium ion battery positive electrode material with high interface conductivity and preparation method thereof

    CN121439765A

  • A lithium ion battery cathode material with high interfacial conductance and a preparation method thereof

    CN121439765B